Pengaruh Beban Kerja dan Motivasi Terhadap Kepuasan Kerja Pegawai di Kejaksaan Negeri Raba Bima: The Influence of Workload and Motivation on Employee Job Satisfaction at the Raba Bima District Attorney's Office - Wulan, Dian Nawa; Yusuf, Muhammad; Rahmatia, Rahmatia (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine the influence of workload and motivation on the job satisfaction of employees at the Raba Bima District Attorney's Office. The research instrument used a Likert scale questionnaire. The research population consisted of 56 respondents, from which a sample of 34 respondents was obtained using a purposive sampling technique. Data were collected through observation, questionnaires, and a literature review. The data were analyzed using multiple linear regression. The results of the study indicate that workload and motivation have a significant influence on the job satisfaction of employees at the Raba Bima District Attorney's Office.